Characterization of the mitochondrial genomes of three powdery mildew pathogens reveals remarkable variation in size and nucleotide composition. Issue 12 (10th December 2021) - Zaccaron, Alex Z.; Stergiopoulos, Ioannis
Abstract : Powdery mildews comprise a large group of economically important phytopathogenic fungi. However, limited information exists on their mitochondrial genomes. Here, we assembled and compared the mitochondrial genomes of the powdery mildew pathogens Blumeria graminis f. sp. tritici, Erysiphe pisi, and Golovinomyces cichoracearum . Included in the comparative analysis was also the mitochondrial genome of Erysiphe necator that was previously analysed. The mitochondrial genomes of the four Erysiphales exhibit a similar gene content and organization but a large variation in size, with sizes ranging from 109800 bp in B. graminis f. sp. tritici to 332165 bp in G. cichoracearum, which is the largest mitochondrial genome of a fungal pathogen reported to date. Further comparative analysis revealed an unusual bimodal GC distribution in the mitochondrial genomes of B. graminis f. sp. tritici and G. cichoracearum that was not previously observed in fungi. The cytochrome b ( cob ) genes of E. necator, E. pisi, and G. cichoracearum were also exceptionally rich in introns, which in turn harboured rare open reading frames encoding reverse transcriptases that were likely acquired horizontally. Golovinomyces cichoracearum had also the longest cob gene (45 kb) among 703 fungal cob genes analysed. Collectively, these results provide novel insights into the organization of mitochondrial genomes of powdery mildew pathogens and represent valuable resources for population genetics and evolutionary studies.